하수처리시설의 Retrofitting을 위한 파일럿 규모 공기부상공정 연구 - 박찬혁; 홍석원; 이상협; 최용수 (대한상하수도학회, 2008)
The pilot study was conducted to evaluate the applicability of air flotation(AF) processes combined with biological nutrient removal(BNR) for the retrofitting of conventional wastewater treatment facilities. The BNR system was operated in pre-denitrification and intermittent aeration; developed ceramic membrane diffusers were installed to separate the solid-liquid of activated sludge at the bottom of a flotation tank. Before performing a pilot scale study, the size distribution of microbubbles generated by silica or alumina-based ceramic membrane diffusers was tested to identify the ability of solid-liquid separation. According to the experimental results, the separation and thickening efficiency of the alumina-based ceramic membrane diffuser was higher than the silica-based ceramic membrane diffuser. In a 100m3/d pilot plant, thickened and return sludge concentration was measured to be higher than 15,000mg SS/L, therefore, the MLSS in the bioreactor was maintained at over 3,000mg SS/L. The effluent quality of the AF-BNR process was 4.2mg/L, 3.7mg/L, 10.6mg/L and 1.6mg/L for BOD5, SS, T-N and T-P, respectively. Lastly, it was revealed that the unit treatment cost by flotation process is lower than about 1won/m3 compared to a gravity sedimentation process.